Effect of dislocations on the growth of p‐type GaN and on the characteristics of p–n diodes. Issue 8 (24th February 2017) - Usami, Shigeyoshi; Miyagoshi, Ryosuke; Tanaka, Atsushi; Nagamatsu, Kentaro; Kushimoto, Maki; Deki, Manato; Nitta, Shugo; Honda, Yoshio; Amano, Hiroshi
Abstract : We investigate the influence of crystal defects on p‐type GaN grown by metalorganic vapor phase epitaxy. Sets of p‐type GaN films were grown on sapphire substrates and on free‐standing GaN (F‐GaN) substrates simultaneously using various Et‐Cp2 Mg flow rates. Although there is a difference of two orders of magnitude between the threading dislocation densities of p‐type GaN grown on sapphire and F‐GaN substrates, there is no significant difference in hole concentration. However, there are problems with the surface morphology of p‐type GaN grown on sapphire. The deterioration of the surface was caused by the difference in nanopipe density. The electrical properties of a p–n junction diode formed on sapphire with a high density of nanopipes were observed using emission microscopy under both forward‐ and reverse‐bias conditions. Our results demonstrate that the nanopipes are electrically inactive, and that other types of threading dislocation have more influence on the current–voltage characteristics.